Synergistic Interactions between Mammalian Antimicrobial Defense Peptides - Yan, Hong (American Society for Microbiology, 2001)
A single animal can express several cationic antimicrobial peptides with different sequences and structures. We demonstrate that mammalian peptides from different structural classes frequently show synergy with each other and selectively show synergy with human lysozyme.